JARINGAN SYARAF TIRUAN MEMPREDIKSI TINGKAT PENJUALAN SEPEDA MOTOR MENGGUNAKAN METODE BACKPROPAGATION (STUDI KASUS : CV.SATU HATI PERKASA) - Latifah Hanum (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2021)
Artificial neural networks are a branch of AI (Artificial Intelligence). Artificial neural network is an information processing paradigm which is inspired by the human brain system in receiving information and solving problems by carrying out the learning process through changes in the weight of its synapses. Motorbikes are one of the important land transportation at this time like a pkok thing which can help them do their activities, especially at work. Therefore, motorcycle manufacturers are competing to create motorbikes with different advantages and advantages so that in the market the number of motorbikes is very large and varied. Motorcycle sales, using motorcycle sales data for 4 years, from 2015 to 2019. Sales data will be processed by the network, in the form of the number of motorcycle sales each month. The data needed in this artificial neural network analysis process is the result of a pure database by taking the input variable in the form of motorcycle sales with the Honda brand and the number of motorcycle sales for the following month as output. In other words, the prediction of motorcycle sales predictions for 3 years is processed into the matlab using the GUI facility, to produce information on the prediction of motorcycle sales that has increased with an average prediction of 27.5185 per month from old data with an average of 25, 75 per month